Nilai-Nilai Budaya Sekolah dalam Pembinaan Aktivitas Keagamaan Siswa SD IT Bunayya Padangsidimpuan - Fitri Rayani Siregar (Jurnal Kajian Gender dan Anak, 2018)
School as the teaching and learning process which the teachers guide students to have a good attitude, behaviour, and manner. The culture value is also related to shape the students’ good characteristics. In this research, the researcher tried to find out what the culture values are that was applied in SD IT Bunayya Padangsidimpuan in religious activities guidance, how the school elements applied them, and whether there were some problems in appliying those values. Therefore, based on the researcher’s findings, it was found that there were many good of culture values that was showed in this school, like; smiling culture, “salam, sapa, sopan, santun or 5S” (greeting, saying, politeness, and good manner),  Nafi’un li Ghorihi culture or environment careness. Beside it, praying together, memorizing holy Qur’an, shiroh, celebrating the great day of Moslem, faith and taqwa guidance at night, giving something to the poor men, doing Qur’ban, and “Pesantren Kilat”. The last, some of the problems found in the research application were from their parents and lack of school facilities.